Bond strength of zirconia- or polymer-based copings cemented on implant-supported titanium bases - an in vitro study - Eliann Oddbratt; Lisa Hua; Bruno R. Chrcanovic; Evaggelia Papia (Medical Journals Sweden, 2021)
Purpose To evaluate the bond strength between polymer-based copings and zirconia copings as positive control, cemented on implant-supported titanium bases with different adhesive cement systems. Moreover, to evaluate if airborne-particle abrasion of polymethylmetacrylate (PMMA) would enhance the bond strength. Methods Four groups of different materials were used to fabricate the copings, 30 in each group: airborne-particle abraded milled zirconia (TAZirconia, control group), milled PMMA (TPMMA), airborne-particle abraded milled PMMA (TAPMMA) and 3 D-printed micro filled hybrid resin (TAMFH). Each group of copings was cemented on titanium bases by three different adhesive cement systems, 10 each: Multilink Hybrid Abutment, Panavia V5, RelyX Ultimate. The specimens were stored dry at room temperature for 24 h, subjected to thermocycling for 5000 cycles followed by evaluating the bond strength by tensile strength test. Results TPMMA and TAPMMA cemented with Multilink Hybrid Abutment showed statistically significant lower bond strength in comparison to TAZirconia and TAMFH. No difference was observed between the latter two. TPMMA, TAPMMA and TAMFH had a statistically significant lower bond strength compared to the control group when cemented with Panavia V5. TPMMA and TAPMMA cemented with Rely X Ultimate showed statistically significant lower bond strength in comparison to the control group. Conclusion Almost all experimental groups, except 3 D-printed MFH, performed inferior than the positive control group where the highest bond strength was reported for the cementation of zirconia copings cemented with Panavia V5 or Rely X Ultimate. Airborne-particle abrasion did not improve the bond strength of the PMMA, except when Multilink Hybrid Abutment was used.